Recent Progress on Activatable Nanomedicines for Immunometabolic Combinational Cancer Therapy. Issue 2 (13th September 2020) - Zhang, Chi; Pu, Kanyi
Abstract : Tumor metabolism generally involves the generation of immunosuppressive metabolites, which contribute to the dysfunction of immune cells. Thus, immunometabolic interventions targeting the metabolic circuits and reducing immunosuppressive metabolites have been developed to invigorate antitumor immunity and attenuate cancer immune evasion. Although several clinical trials have been launched to develop metabolic agents for immunotherapy, they have the issues of potential immune‐related adverse events and low response rate. Smart nanomedicines integrated with physiological stimuli‐activatable action hold great promise to improve the therapeutic effectiveness and reduce systemic side effects for clinical translation. In this review, the recent progress on smart nanosystems for immunometabolic cancer therapy is summarized and their synergistic effects by combining immunometabolic intervention with multiple therapeutic modalities are highlighted, focusing on the molecular design and nanoengineering fabrication of these physiological stimuli‐activatable nanomedicines. These nanomedicines recover their activity of immunometabolic intervention in response to the specific physiological stimuli in the tumor microenvironment. This greatly reinforces their therapeutic action and reduces the off‐target side effects via local reprogramming of tumor metabolism. In addition to highlighting the synergistic therapeutic potential by combining immunometabolic therapy with multiple therapeutic modalities, current challenges and prospects of these activatable nanomedicines are discussed. Abstract : Activatable immunometabolic nanomedicines that reprogram tumor metabolic circuits to invigorate antitumor immunity in response to cancer‐associated physiological stimuli can greatly reinforce their therapeutic action and reduce the off‐target side effects. Herein, the recent progress on activatable nanomedicines is summarized and their synergistic effects by combining immunometabolic intervention with multiple therapeutic modalities for cancer therapy are highlighted.